Differential effects of ascorbic acid on monocytic cell morphology and protein modification: Shifting from pro-oxidative to antioxidant properties - Prasad, Ankush; Rathi, Deepak; Sedlářová, Michaela; Manoharan, Renuka Ramalingam; Průdková, Eliška; Pospíšil, Pavel (Biochemistry and biophysics reports, 2024)
In this study, we investigated the properties of ascorbic acid (vitamin C), which is a naturally occurring water-soluble vitamin. Our goal is to evaluate its pro-oxidative and/or antioxidant capabilities. To do this, we initially used a confocal laser scanning microscope (CLSM) to visualize the differentiation pattern in U-937 cells under the treatment of variable concentrations of ascorbic acid. Prior to induction, U-937 cells showed a spherical morphology. After treatment, significant morphological changes were observed in the form of prominent pseudopodia and amoeboid structures. Interestingly, pseudopodia incidences increased with an increase in ascorbic acid concentrations. In addition, our analysis of protein modification using anti-malondialdehyde antibodies showed changes in more than one protein. The findings reveal the link between the differentiation of U-937 cells into macrophages and the protein modifications triggered by the production of reactive oxygen species when U-937 cells are exposed to ascorbic acid. Furthermore, the transformation of ascorbic acid from a pro-oxidative to an antioxidant property is also demonstrated.
Keywords: Human cells; Reactive oxygen species; Pro-oxidant; Vitamin C; Antioxidants